Customer Delight, Repurchase Intentions and the Mediating Effect of Positive Word of Mouth - Kageyama, Yoshimasa; Barreda, Albert A. (Journal of Research in Marketing (ISSN: 2292-9355), 2018)
The aim of this study is to examine how customer delight, a proven construct superior to the famous customer satisfaction, affects consumers to generate positive word of mouth and to behave positively to repurchase from the brand. The study also tests the mediating effect of positive word of mouth on the delight-repurchase relationship. The theory-driven model includes customer delight, positive word of mouth, and repurchase intentions. The study involves the participation of 302 consumers to examine the proposed hypotheses. Study findings suggest that customer delight is a significant predictor of positive word of mouth and intentions to buy from the brand of preference. The results also support the notion that positive word of mouth mediate the impact of customer delight on repurchase intentions. Additionally, the study shows that once positive word of mouth is introduced in the model for analysis, it helps to increase substantially the variance explained in dependent variable named repurchase intentions. This study advances the service marketing literature explaining the effect of emotion-customer delight, and the mediating role of positive word of mouth.